Effect Of Different Supported Heteropoly Acid On The Catalytic Hydrothermal Conversion Of Cellulose Into Formic Acid - Nor Liyana Zakira Zabidi Adi @ Zaibidai Adil; Azzusyaza Azhari; Tengku Shafazila Tengku Saharuddin; Farah Wahida Harun (Trans Tech Publications, 2024)
Indexed by Scopus/ERA